Given "(x+y)(p+q) =z-1"
"\\implies (x+y)p + (x+y)q = z-1"
So, Lagrange's equation is
"\\frac{dx}{x+y} = \\frac{dy}{x+y} = \\frac{dz}{z-1}" .
By First two factors of Lagrange's equation
"\\frac{dx}{x+y} = \\frac{dy}{x+y} \n\\\\\n\\implies dx = dy \\\\\n\\implies x - y =c_1" ______________(1)
By last two factors, we get
"\\frac{dy}{x+y} = \\frac{dz}{z-1}"
Now, by using solution (1), we get
"\\frac{dy}{c_1+2y} = \\frac{dz}{z-1}"
By integrating, we get
"\\frac{1}{2}\\log(c_1+2y) = \\log(z-1)+c_2"
"\\implies \\frac{1}{2}\\log(x+y) = \\log(z-1)+c_2"
"\\implies 0 = \\log(\\frac{z-1}{\\sqrt{x+y}})+c_2"
"\\implies \\frac{z-1}{\\sqrt{x+y}} = e^{-c_2} = c_3" ____________(2)
Hence, Solution is "c_3 = f(c_1)"
"\\implies z-1 = (\\sqrt{x+y}) \\ f(x-y)"
Comments
Leave a comment